Improving Oral Health for the Elderly An Interdisciplinary Approach - Lamster, Ira B.; Northridge, Mary E. (Springer New York : Imprint: Springer, 2008)
Improving Oral Health for the Elderly: An Interdisciplinary Approach Edited by Ira B. Lamster, Columbia University College of Dental Medicine, New York Mary E. Northridge, Mailman School of Public Health, Columbia University, New York Improving Oral Health for the Elderly: An Interdisciplinary Approach examines in depth a crucial yet frequently overlooked indicator of seniors' quality of life. By combining a lifespan approach to health with a biopsychosocial perspective on health disparities, this book places oral health in the larger context of physical and mental well-being. Chapter authors emphasize elders' distinct needs as a group, the interplay of factors contributing to the oral disease burden (from increased tooth retention to the absence of dental benefits as part of Medicare), and the necessity-and overall benefits-of improved service delivery and interdisciplinary care. The result is an invaluable set of recommendations to the clinical, research, and administrative communities that they can use to better understand and serve this steadily growing population. Among the topics covered: Access to oral health care. Common illnesses and conditions affecting seniors' oral health. Normal oral/dental changes associated with aging. Oral health care considerations for older adults. Educating the dental profession. Emerging research and policy issues. Plus specific chapters on periodontal disease as a risk factor for systemic diseases, oral cancer, and orofacial pain. Improving Oral Health for the Elderly: An Interdisciplinary Approach is of immediate interest to readers in dentistry, medicine, and aging studies, but this unique volume also merits the attention of professionals and researchers involved in community and public health, health promotion, disease prevention, social work, health care policy and planning.